1998
DOI: 10.1016/s0014-5793(98)00410-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of γ‐glutamylcysteine synthethase‐heavy subunit promoter: a critical role for AP‐1

Abstract: The 5P-flanking region of human Q Q-glutamylcysteine synthetase-heavy subunit (Q Q-GCS-HS) was characterised by creating a series of chloramphenicol acetyl transferase (CAT) reporter deletion constructs. Analysis of various deleted CAT constructs revealed that a putative AP-1 consensus sequence is required to direct the constitutive and oxidant-mediated promoter activity. Gel mobility shift and mutation analysis of the sequence (3269 to 3263 bp), showed binding of AP-1 is involved in the oxidant-mediated regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
70
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 24 publications
7
70
0
Order By: Relevance
“…Blocking AP-1 activity led to a fall in the basal mRNA level of all three genes and their constitutive promoter activities. This finding is similar to what has been reported also for the human GCL subunit promoters and GCLC mRNA level, where AP-1 activity is required for constitutive activity and basal expression (27)(28)(29). However, blocking AP-1 activity also blocked significantly the TBH-mediated increase in the promoter activity of the rat GCL subunits and GS as well as the mRNA levels of all three genes.…”
Section: Figsupporting
confidence: 90%
“…Blocking AP-1 activity led to a fall in the basal mRNA level of all three genes and their constitutive promoter activities. This finding is similar to what has been reported also for the human GCL subunit promoters and GCLC mRNA level, where AP-1 activity is required for constitutive activity and basal expression (27)(28)(29). However, blocking AP-1 activity also blocked significantly the TBH-mediated increase in the promoter activity of the rat GCL subunits and GS as well as the mRNA levels of all three genes.…”
Section: Figsupporting
confidence: 90%
“…We next elucidated the transcriptional regulatory mechanism by which TNF-␣ exerted its effect on the induction of ␥-GCS-HS. By using deletion and mutation studies, we have recently shown the critical role of a putative AP-1 site in oxidant-mediated regulation of the ␥-GCS-HS promoter (15). However, other investigators have suggested that an NF-Bbinding site in the ␥-GCS-HS promoter may be important in regulating ␥-GCS-HS gene expression (40,42).…”
Section: Discussionmentioning
confidence: 99%
“…A HindIII and SphI fragment (1138 bp) containing the promoter was isolated and subcloned into the polylinker of the promoterless plasmid pCAT Basic Vector (Promega). This construct was denoted pCBGCS and has been described previously (15,26,27).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations